Evidentiality in the Age of Multimodal Communication: a Linguosynergetic Analysis of Mass Media Texts - D. V. Kozlovsky (Дискурс профессиональной коммуникации, 2023)
In modern mass media texts, the modus category of evidentiality plays a crucial role in conveying the author’s message and shaping the reader’s perception of the information presented. The use of multimodal means, including nonverbal components of communication, visual modus, and hyperlinks, intensifies and expands evidential semantics, influencing the reader’s judgment of the relevance, reliability, and truthfulness of the information and its source. This study employs linguosynergetic analysis and a range of quantitative, functional-semantic, and contextual-situational methods to investigate how multimodal means contribute to the expression of various shades of evidential meaning, such as reflections, doubts, confidence, statements, and citations. The research material includes discursive contexts from advanced informational, scientific, general research, and practical-analytical articles, as well as definitions from electronic versions of dictionaries of the modern English language. The results suggest that multimodal means serve as valuable additional resources for updating evidential semantics, highlighting the possibility of combining them with various linguistic indicators of the category of evidentiality to achieve the author’s communicative intentions. The article sheds light on the intricacies of evidentiality in mass media discourse and provides insights into the role of multimodal means in conveying meaning beyond words.